Auditive Navigation System for Visually Impaired Individuals in Indoor Spaces Using Augmented Reality (2023)
Visual impairment affects individuals with complete or partial loss of vision. Visually impaired students in Colombian educational institutions face challenges when navigating indoors due to the lack of braille signage. This paper presents the development, implementation, and testing of an augmented reality (AR)-based mobile app that uses rMQR codes to play acoustic descriptions of locations. The application enhances the independence and mobility of visually impaired students in academic spaces. The process involved designing a navigation system, developing software using Unity and Vuforia, and evaluating the application's functionality, accuracy, stability, and performance. A group of thirty-six (36) students validated the software, and their feedback was gathered through a questionnaire using a 5-Likert scale. The results showed that the app had an accessible interface, provided useful information about spaces, and improved autonomy and safety. The app demonstrated fast and accurate code scanning, and its effectiveness in promoting independence, meeting expectations, and not interfering with mobility was validated. The findings emphasize the potential of AR-based applications in supporting visually impaired individuals and fostering social inclusion.